Prevalence and predictive factors for exclusive breastfeeding in the first 6 months among mothers attending Primary Health Care Centers in Cairo, Egypt - Emara, Zeinab Abdelhay; Amin, Ghada Essam Eldin; Hamid, Diaa Marzouk Abdel; Allam, Mohamed Farouk (European Journal of Clinical and Experimental Medicine, 2021)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Although most organizations recommend breastfeeding for at least one year due to its well-known beneficial effects, the prevalence of exclusive breastfeeding in many developing countries was quite low. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To identify prevalence and predictive factors affecting exclusive breastfeeding in Primary Healthcare (PHC) Centers in Cairo, Egypt. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A cross-sectional study, among mothers attended first six months immunization sessions in three PHC Centers were selected via a convenient sample, A total sample of 180 mothers, 60 from each PHC Center, were subjected to an interview questionnaire. The questionnaire used was previously validated and pre-tested. Data collection took the period from April to August 2019. Comparison between exclusive and nonexclusive breastfeeding according to possible risk factors was done. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The frequency of breastfeeding among the participants was 90.6%; however the total exclusive breastfeeding frequency was only 39.4%. Our logistic regression model showed that exclusive breastfeeding decreased with progressive increase in infant’s age (OR 0.74), and mothers with good knowledge about proper practice of breastfeeding adhered more to exclusive breastfeeding (OR 2.51). Also, it showed that, during working hours, mothers who fed their infants other than breast milk adhered less to exclusive breastfeeding (OR 0.19). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The prevalence of exclusive breastfeeding is quite low. The predictive factors for exclusive breastfeeding are, younger infant’s age, good knowledge of the mothers about proper practice of breastfeeding, and mothers insisting on breastfeeding during working hours.